The Impact of Air Pollution on Lung Development and Physical Growth in Early Childhood: A Systematic Review of Risk Factors and Long-Term Effects - Labetubun, Nia Sahra; Mafazi, Hashfi; Ariani (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Children in developing countries are highly vulnerable to respiratory health problems caused by air pollution. Exposure during pregnancy and early life critically influences lung development and physical growth, with potential long-term consequences. This systematic review aimed to assess the effects of prenatal and early childhood exposure to air pollution on lung development and physical growth, and to identify risk factors that may influence these outcomes. A systematic search was conducted in February 2025 across Scopus, PubMed, and Web of Science databases. Studies published in English between 2015 and 2025 were screened using PRISMA guidelines and assessed for quality using the ROBINS-I tool. From 1,303 records, 28 studies met the inclusion criteria. Twenty-one studies (75%) reported reductions in lung function parameters such as FEV₁, FVC, and FEF25–75% in association with pollutants including PM2.5, NO₂, O₃, and PAHs. Three studies reported increased risk of stunting, primarily linked to indoor air pollution and biomass fuel exposure. These outcomes were associated with mechanisms such as oxidative stress, systemic inflammation, and epigenetic changes. The second trimester of pregnancy and the first two years of life were identified as critical exposure windows. Risk was modified by age, sex, socioeconomic status, breastfeeding duration, and home ventilation. Air pollution exposure during sensitive developmental periods impairs lung function and physical growth in children. Urgent public health measures—promoting clean energy, improving indoor air quality, and reducing exposure in vulnerable groups—are essential to support healthy childhood development.